Preparing patients to undergo surgery - Zlatka Rakovec Felser; Špela Planinc; Marjanca Matvoz; Lea Vidovič (Acta Medico-Biotechnica, 2021)
Purpose: This study aimed to evaluate patient anxiety levels and ways of coping, while they are waiting in the hospital to undergo surgery.Methods: One hundred fifty-four patients were included from four different surgical departments (62 females and 92 males), 24–86 years of age (mean age [M] = 58.8 years). The following instruments were applied: a semi-structured interview; the State-Trait Inventory for Cognitive and Somatic Anxiety; and The Brief Cope Inventory.Results: One-half of the patients (50%) expressed a fear to undergo surgery; 28 % of the patients said that they were afraid of anaesthesia, regarderless of the type of anaesthesia, and 54% of patients expressed a fear and worry about the outcome of surgery. Women (Mas ± SDas =32.58±8.01; Mat ± SDat =35.16±8.97; in general, Ma ± SDa =67.74±15.44) had state and trait anxiety significantly more often than men (Mas ± SDas =28.11±6.21; Mat ± SDat =30.29±7.48; in general Ma ± SDa=58.40±12.74). Elderly males fall due to the received weak social support into the risk group of patients. They less often/less directly express their needs and emotions, and are less active in searching for information or advice in the social environment. In stressful situations, elderly males also frequently give up the attempt to obtain the goals with which the stressor is interfering.Conclusion: Patients who wait to undergo surgery should not suffer anxiety needlessly because it is known that anxiety has a negative impact on the course and outcome of surgical procedures. The pre-operative management of a patient’s anxiety is therefore important and a well-educated medical care team should be familiar with the appearance of anxiety, communication skills, and relaxation treatment.